Efficient CRISPR Mutagenesis in Sturgeon Demonstrates Its Utility in Large, Slow-Maturing Vertebrates - Stundl, Jan; Soukup, Vladimír; Franěk, Roman; Pospisilova, Anna; Psutkova, Viktorie; Pšenička, Martin; Cerny, Robert; Bronner, Marianne E.; Medeiros, Daniel Meulemans; Jandzik, David (Frontiers in Cell and Developmental Biology, 2022)
In the last decade, the CRISPR/Cas9 bacterial virus defense system has been adapted as a user-friendly, efficient, and precise method for targeted mutagenesis in eukaryotes. Though CRISPR/Cas9 has proven effective in a diverse range of organisms, it is still most often used to create mutant lines in lab-reared genetic model systems. However, one major advantage of CRISPR/Cas9 mutagenesis over previous gene targeting approaches is that its high efficiency allows the immediate generation of near-null mosaic mutants. This feature could potentially allow genotype to be linked to phenotype in organisms with life histories that preclude the establishment of purebred genetic lines; a group that includes the vast majority of vertebrate species. Of particular interest to scholars of early vertebrate evolution are several long-lived and slow-maturing fishes that diverged from two dominant modern lineages, teleosts and tetrapods, in the Ordovician, or before. These early-diverging or “basal” vertebrates include the jawless cyclostomes, cartilaginous fishes, and various non-teleost ray-finned fishes. In addition to occupying critical phylogenetic positions, these groups possess combinations of derived and ancestral features not seen in conventional model vertebrates, and thus provide an opportunity for understanding the genetic bases of such traits. Here we report successful use of CRISPR/Cas9 mutagenesis in one such non-teleost fish, sterlet Acipenser ruthenus, a small species of sturgeon. We introduced mutations into the genes Tyrosinase, which is needed for melanin production, and Sonic hedgehog, a pleiotropic developmental regulator with diverse roles in early embryonic patterning and organogenesis. We observed disruption of both loci and the production of consistent phenotypes, including both near-null mutants’ various hypomorphs. Based on these results, and previous work in lamprey and amphibians, we discuss how CRISPR/Cas9 F0 mutagenesis may be successfully adapted to other long-lived, slow-maturing aquatic vertebrates and identify the ease of obtaining and injecting eggs and/or zygotes as the main challenges.